UMP, SSM collaboration succeeds Work-Based Learning Education - Siti Zanariah, Satari; Mimi Rabita, Abdul Wahit (2021)
PEKAN, 9 March 2021 - The collaboration between Universiti Malaysia Pahang (UMP) and the Companies Commission of Malaysia (SSM) signed in the recent Memorandum of Understanding (MoU) Signing Ceremony is able to contribute towards producing quality students to provide services that meet the needs of the industry.